The Yoni of Kamakhya: The Intersection of Power and Gender in its Mythology - Rosati, Paolo E. (Religions of South Asia, 2021)
The mythology of the yoni of Sati was introduced in the early medieval Kalikapurana (ninth–eleventh century ce), a sakta text that linked the sexual symbol of the Goddess to the Kamakhya-pitha in Assam. This article will analyse the medieval Puranas and Tantras compiled in northeastern India—focusing on their mythological accounts of the cosmogony of the yoni pitha—in order to outline a historical evolution of the yoni symbol through the Middle Ages. Combining leftist Freudian, post-structuralist and post-gender theories with religious studies, the yoni will be considered both as a source of power and as a battlefield of sex–gender identity. In conclusion, this article will challenge the idea of a static yoni but will underline a sex–gender evolution of its identity, which encompasses and transcends both male and female powers.